The Influence of Influencer Endorsement and Instagram ads on Purchase Intention Hijab Local Product : Case Study on Lozy Hijab in Surabaya - Az Zahra, Sabrina Aulia; Izaak, Wilma Cordelia (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
The development of social media has encouraged the fashion industry, including the hijab trend as representation of modern Muslim fashion. Pashmina has become one of the most popular hijab styles, and local brands such as Lozy Hijab are utilizing digital marketing strategies, particularly influencer endorsement and Instagram ads to attract consumer purchase intention. This study aims to analyze the influencer endorsement and Instagram ads on the purchase intention of Lozy Hijab’s pashmina products in Surabaya. This research uses a quantitative methods through non-probability sampling with a population of people who live in Surabaya and know Lozy Hijab pashmina products. This research employed purposive sampling method involving 112 respondents. This research uses a likert scale variable measurement technique. The study gathered data through online questionnaires distributed using GoogleForm. The analysis employed Structural Equation Modelling (SEM) using the Partial Least Square (PLS) with SmartPLS software. The analysis involved examining the outer model (including convergent validity, discriminant validity, and composite reliability) alongside the inner model evaluation (r square test, path coefficients). The results of the study that influencer endorsement and Instagram ads had a positive and significant effect on the purchase intention with a significance value 0.000 < 0.05. This means that a relevant influencers and effective Instagram ads, can increase consumer purchase intention in buying pashmina Lozy Hijab products.